(untitled) (Research, Society and Development, 2020)
This article reflects on the Labor Reform, Law No. 13.467 / 2017 in the light of the Universal Declaration of Human Rights, bringing a historical retrospective of human and labor rights, the emergence of the Universal Declaration of Human Rights and Labor Law in Brazil and on the reach by Brazilian workers of rights and guarantees over the years until the Federal Constitution of the Republic of 1988. The methodology is that of bibliographic review. It also reflects on the flexibilization of these rights after the Labor Reform and its consequences on human rights. It appears that many workers’ rights have been changed, such as the provision of work modalities without guarantee of stability, entry in the Work Card or integration with Social Security, possibility of increasing the working day and reducing rest and meal hours.